Integrative analysis highlights molecular and immune responses of tick Amblyomma americanum to Escherichia coli challenge - Lyu, Bo; Li, Jingjing; Niemeyer, Brigid; Anderson, Deborah M.; Beerntsen, Brenda; Song, Qisheng (Frontiers in Cellular and Infection Microbiology, 2023)
Ticks are ectoparasites that can transmit various pathogens capable of causing life-threatening illnesses in people and animals, making them a severe public health threat. Understanding how ticks respond to bacterial infection is crucial for deciphering their immune defense mechanisms and identifying potential targets for controlling tick-borne diseases. In this study, an in-depth transcriptome analysis was used to investigate the molecular and immune responses of Amblyomma americanum to infection caused by the microinjection of Escherichia coli. With an abundance of differentially expressed genes discovered at different times, the analysis demonstrated significant changes in gene expression profiles in response to E. coli challenge. Notably, we found alterations in crucial immune markers, including the antimicrobial peptides defensin and microplusin, suggesting they may play an essential role in the innate immune response. Furthermore, KEGG analysis showed that following E. coli exposure, a number of key enzymes, including lysosomal alpha-glucosidase, fibroblast growth factor, legumain, apoptotic protease-activating factor, etc., were altered, impacting the activity of the lysosome, mitogen-activated protein kinase, antigen processing and presentation, bacterial invasion, apoptosis, and the Toll and immune deficiency pathways. In addition to the transcriptome analysis, we constructed protein interaction networks to elucidate the molecular interactions underlying the tick’s response to E. coli challenge. Hub genes were identified, and their functional enrichment provided insights into the regulation of cytoskeleton rearrangement, apoptotic processes, and kinase activity that may occur in infected cells. Collectively, the findings shed light on the potential immune responses in A. americanum that control E. coli infection.